Diplura in caves: diversity, ecology, evolution and biogeography. Issue 3 (27th November 2020) - Sendra, Alberto; Palero, Ferran; Jiménez-Valverde, Alberto; Reboleira, Ana Sofia P S
Abstract: Diplurans (Hexapoda) are considered the 'ideal cavernicolous animal' having one of the highest ratios of cave-adapted vs. non-cave-adapted species. They are successful colonizers of subterranean habitats, thriving in all cryptic, dark, terrestrial environments. Diplurans play an important role in the decomposition of organic matter below the ground and are sensitive to anthropogenic pressures. We present the first comprehensive review about cave Diplura diversity, ecology, evolution, distribution and biogeography. We provide a roadmap for research questions regarding the ecology, aimed at stimulating the pursuit of new studies on this fascinating group. Filling these current knowledge gaps will contribute to conservation efforts for cave ecosystems.